Astrovirus induced nonpurulent encephalomyelitis in sheep: First report from Türkiye by high-throughput sequencing - Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Shams, Farzane; Seuberlich, Torsten; Karabulut, Burak; Incili, Canan Akdeniz; Eroksuz, Hatice (Wiley, 2024)
BackgroundThis study presents the case of non-purulent encephalomyelitis associated with astrovirus infection in a sheep from Eastern Anatolia, T & uuml;rkiye.MethodsA necropsy was performed on a sheep showing nervous signs. Afterwards, brain tissue samples were taken and examined with histopathological, immunohistochemical and molecular techniques.ResultsNeuropathologic changes included neuronal degeneration, diffuse gliosis, multifocal perivascular cuffing, neuronophagy and neuronal necrosis in the cerebrum, the cerebellum and the cervical spinal cord. Aerobic and anaerobic bacterial culture, selective culture for Listeria monocytogenes, and PCR analysis for rabies virus, tick-borne encephalitis virus, T & uuml;rkiye encephalitis virus, small ruminant lentiviruses and border disease virus were negative. However, the presence of astrovirus RNA in cerebral, cerebellar and spinal cord samples was demonstrated by a pan-astrovirus RT-PCR. Immunohistochemical examinations revealed astrovirus antigens within the neuronal cytoplasm. High-throughput sequencing techniques identified the causative agent as a member of the genotype species Mamastrovirus 13 but representing a distinct genetic lineage with similarity to ovine astrovirus 1 in the open-reading frames (ORF)1ab region and muskox astrovirus in the ORF2 region.ConclusionThis report provides evidence that astroviruses are potentially encephalitis-causing pathogens in ovine populations in T & uuml;rkiye, featuring an astrovirus strain distinct from those previously identified in sheep. The case of non-purulent encephalomyelitis associated with astrovirus infection in a sheep presented. Histopathological examination reveals signs of encephalitis, and astrovirus was detected by PCR. image
Keywords: astrovirus; encephalitis; high-throughput sequencing; immunohistochemistry; non-purulent encephalomyelitiss